EKSISTENSI DAN KEHUJJAHAN YURISPRUDENSI PENGADILAN AGAMA SEBAGAI SUMBER HUKUM - Baidlowi Baidlowi (Indonesian Journal of Law and Islamic Law (IJLIL), 2021)
One of the legal systems adopted in Indonesia is the common law system. In this legal system, the law is not bound by formal procedures. Even more, law interacts with people's lives or in another sense, law is a formation of the culture (culture) of society. Therefore, in this system, judges in the judiciary, both in general, religious, military and state administration are given full authority to create laws (judge made law). This case can also occur in the Religious Courts as executors of the Religious Courts. Where the judges in the Religious Courts, of course, also have the same capability and right to create laws as judges in other courts. From this, the possibility of the emergence of Jurisprudence can be expected. Because the judge has been in the process of exercising the authority that has been given to him to create laws. With the ability of judges to create a law, finally the author's mind appears regarding the problem related to the existence of jurisprudence as a source of PA law and the problem is usually a jurisprudence - which is the result of a judge's ijtihad in punishing a case - to be used as a legal foothold in decision making in the court environment. Religion, in particular, is related to its honesty when compared to Islamic jurisprudence (Fiqh). This journal writing method is based on literature and literature reviews that discuss the issue of jurisprudence.